The contribution of astrocytes to the regulation of cerebral blood flow - Howarth, Clare (Frontiers in Neuroscience, 2014)
In order to maintain normal brain function, it is critical that cerebral blood flow (CBF) is matched to neuronal metabolic needs. Accordingly, blood flow is increased to areas where neurons are more active (a response termed functional hyperemia). The tight relationships between neuronal activation, glial cell activity, cerebral energy metabolism and the cerebral vasculature, known as neurometabolic and neurovascular coupling, underpin functional MRI (fMRI) signals but are incompletely understood. As functional imaging techniques, particularly BOLD fMRI, become more widely used, their utility hinges on our ability to accurately and reliably interpret the findings. A growing body of data demonstrates that astrocytes can serve as a ‘bridge’, relaying information on the level of neural activity to blood vessels in order to coordinate oxygen and glucose delivery with the energy demands of the tissue. It is widely assumed that calcium-dependent release of vasoactive substances by astrocytes results in arteriole dilation and the increased blood flow which accompanies neuronal activity. However, the signaling molecules responsible for this communication between astrocytes and blood vessels are yet to be definitively confirmed. Indeed, there is controversy over whether activity-induced changes in astrocyte calcium are widespread and fast enough to elicit such functional hyperemia responses. In this review, I will summarise the evidence which has convincingly demonstrated that astrocytes are able to modify the diameter of cerebral arterioles. I will discuss the prevalence, presence and timing of stimulus-induced astrocyte calcium transients and describe the evidence for and against the role of calcium-dependent formation and release of vasoactive substances by astrocytes. I will also review alternative mechanisms of astrocyte-evoked changes in arteriole diameter and consider the questions which remain to be answered in this exciting area of research.